Commodities Pricing and the Bulk Trap Learnings from Industries at the Forefront - Andrén-Sandberg, Fredrik (Springer International Publishing, 2018)
This book takes a fresh look at pricing, product differentiation and the need for decommoditisation in market sectors where products and services are standardised and interchangeable. In the first chapters the book explains what commodities are, and puts them into a historical perspective to promote an understanding of their production and its effects. From this baseline the book then presents a case study on how decommoditisation has progressed within the energy industry. Building on this case study and learnings from other sectors, it develops a theoretical framework, characterising the processes and mechanisms observed to be extended towards different industries. This framework is then utilised in the following chapters as a model to explain the progression of decommoditisation, and to examine other sectors through this lens. To conclude, the book presents the implications for stakeholders and suggestions on how to respond to them from a policy and business standpoint. In a final chapter the book develops an outlook on current trends and possible alternative pathways, and summarizes the main takeaways for management professionals and policymakers alike. .